Beauty of Sports and Beauty in Sports: to the Question of Aesthetic Preparation of Athletes - Ubbiev Baxit (Zien Journals, 2022)
Objective of the study was to probe the aesthetic education standards in student community and their need for basic aesthetic education in the physical education curriculum. Methods and structure of the study. We sampled for the questionnaire survey the 4year students (n=120) from the KSU of Physical Culture’s Departments majoring in Physical Education discipline. Results and conclusion. Having analyzed the questionnaire survey data in the context of the ongoing aestheticization of the professional sports, we would make the following preliminary conclusions. First it should be emphasized that the physical education faculties and students recognize the need for modern aesthetic education in the professional training systems, with such education being particularly beneficial for the sports managing community. Second, there is a clear need for a broad discussion of a basic aesthetic education curriculum for the physical education universities – that should cover the whole academic study period on an uninterrupted basis.
Keywords: beauty; professional sport; attraction; aesthetic education